Extension and Validation of A Novel Destination Brand Equity Model. (July 2023) - Ekinci, Yuksel; Japutra, Arnold; Molinillo, Sebastian; Uysal, Muzaffer
This study develops and tests a novel destination brand equity model and compares its validity with Aaker's brand equity model, which is popular in tourism. The data were collected in Indonesia ( n = 250) and the United Kingdom ( n = 246). The results confirm validity and hierarchical structure of the destination brand equity model. The destination brand equity model has seven dimensions: brand awareness, physical quality, service interaction quality, brand self-congruence, brand identification, destination brand trust, and destination brand loyalty. The first five brand equity dimensions exert positive influences on destination brand trust and destination brand loyalty. The findings show that the psychometric properties of the destination brand equity model outperform Aaker's model. The study discusses theoretical and practical implications of the destination brand equity model for destination marketing and management.